1980
DOI: 10.1063/1.327582
|View full text |Cite
|
Sign up to set email alerts
|

Dopant segregation in polycrystalline silicon

Abstract: Dopant segregation at grain boundaries in poly crystalline silicon has been investigated. Arsenic, phosphorus, and boron were ion implanted into low-pressure, chemically-vapor-deposited polycrystalline-silicon films. All films were then annealed at 1000·C for 1 h, and some were subsequently further annealed at 800, 850, or 900 DC for 64, 24, or 12 h, respectively. For phosphorus and arsenic the room-temperature resistivity of the films was found to be higher after annealing at lower temperatures. By successive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
107
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 377 publications
(118 citation statements)
references
References 24 publications
11
107
0
Order By: Relevance
“…The measured values for the resistivity and for the temperature coefficient are of the same order of magnitude as those found in the literature [23,24,29,30,321. The strong decrease in resistivity after annealing for 30 s or less, or after annealing at low temperatures, see Fig.…”
Section: Discumionsupporting
confidence: 75%
“…The measured values for the resistivity and for the temperature coefficient are of the same order of magnitude as those found in the literature [23,24,29,30,321. The strong decrease in resistivity after annealing for 30 s or less, or after annealing at low temperatures, see Fig.…”
Section: Discumionsupporting
confidence: 75%
“…Although the grain boundary barriers are similar for nand p-type polycrystalline silicon layers, dopant segregation can lead to differences in electrical behavior. Mandurah et al 21 have shown that As and P segregate to grain boundaries whereas B does not. This can cause differences in conduction since segregated dopant is electrically inactive and hence cannot reduce the grain boundary energy barrier.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the fact that at the highest hot-pressing temperature of 1050 • C the segregation of P at the surface of Si NCs becomes rather effective. 16 Segregated P may form precipitates, retarding the viscous flow of melt small Si NCs or surface oxide. Clearly, this effect is more serious as the concentration of P is higher.…”
Section: Methodsmentioning
confidence: 99%